A decision support approach employing the PROMETHEE method and risk factors for critical supply assessment in large-scale projects. (2022) - da Cunha, Richard Alex; Rangel, Luís Alberto Duncan; Rudolf, Christian A.; Santos, Luiza dos
Highlights: Identification of critical risk factors that impact supply chains of large-scale projects A mathematical model developed that establishes the prioritization of supplies of critical equipment throughout the lifecycle of Large-scale projects. Managers and organizations can adopt this solution as a practical and dynamic tool to support decision-making in the definition of possible critical supply scenarios. Abstract: The purpose of this article is twofold: to identify the critical risk factors (RFs) that impact supply chains (SC) in the engineering, procurement, and construction of large-scale projects (EPC-LSP) of the oil and gas industry (OGI) and to apply these RFs in a mathematical model developed, based on multiple-criteria decision-making (MCDM) methods in an expert group. The mathematical model was developed in MATLAB and was based on the Preference Ranking Organization Method for Enrichment Evaluations (PROMÉTHÉE) II and (PROMÉTHÉE GDSS) Group Decision Support System methods. The model's criteria were defined with the RF mapping identified using 33 years of literature and the application of questionnaires to specialists. The evaluation process of the alternatives concerning the defined criteria was conducted through questionnaires to specialists. Finally, the functionality and results of the model were validated by the specialists in the field through interviews. As a contribution, managers, companies, and industry could adopt this solution as a practical and dynamic tool to support decision-making. This fact especially holds true in possible critical supply scenarios, where it is necessary to direct resources to minimize risks and other impacts to EPC-LSP SC. Another novelty refers to the critical risk factors identified, originating from an extensive literature mapping covering the three pillars of sustainability. Moreover, this research was to fill the literature gap, given the lack of studies that propose clear, practical, and specific tools for SCRM in EPC-LSP.